2003
DOI: 10.1063/1.1558216
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled vertical GaN nanorods grown by molecular-beam epitaxy

Abstract: Dislocation-free vertical GaN pillars in nanoscale were grown on Si (111) surface through self-assembly by molecular-beam epitaxy. No extra catalytic or nanostructural assistance has been employed. These nanorods have a lateral dimension from ≲10 nm to ∼800 nm and a height of ≲50 nm to ≳3 μm protruding above the film, depending on the growth parameters. The top view of the nanorods has a hexagonal shape from scanning electron microscopy. Transmission electron microscopy shows that the nanorods are hexagonal, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
88
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 21 publications
2
88
1
Order By: Relevance
“…These nanocolumns were independently grown with their c-axis perpendicular to the substrate surface. Until now, many studies on nitride nanoscale columnar structures have been reported, for example, growth of nanocolumns by ECR-MBE [4] and HVPE [5], fabrication of nanocolumns by reactive ion etching [6] and photon-assisted anodic etching [7], growth on (111) Si substrate [8], evaluation of optical properties [9,10], growth of GaN/AlGaN [11,12] and InGaN/GaN [1] quantum wells in the nanocolumns, and so on. In this paper, we describe the optical properties of GaN nanocolumns using room temperature photoluminescence, under low and high (photopump) excitation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These nanocolumns were independently grown with their c-axis perpendicular to the substrate surface. Until now, many studies on nitride nanoscale columnar structures have been reported, for example, growth of nanocolumns by ECR-MBE [4] and HVPE [5], fabrication of nanocolumns by reactive ion etching [6] and photon-assisted anodic etching [7], growth on (111) Si substrate [8], evaluation of optical properties [9,10], growth of GaN/AlGaN [11,12] and InGaN/GaN [1] quantum wells in the nanocolumns, and so on. In this paper, we describe the optical properties of GaN nanocolumns using room temperature photoluminescence, under low and high (photopump) excitation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…12 As illustrated in Fig. 1, the hexagonal, prismatic-shaped nanorod is generated by cutting from the bulk GaN WZ structure with lattice constants a = 3.23 Å and c = 5.16 Å.…”
mentioning
confidence: 99%
“…12 Transmission electron microscopy observations show that as-synthesized GaN nanorods have hexagonal cross sections along the c-axis. 12 As illustrated in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] In the past two decades, reports on GaN films grown by chemical vapor deposition ͑CVD͒ or molecular beam epitaxy ͑MBE͒ have dominated thanks to the relative ease of achieving electronic-grade epitaxial films. 3,4,6 A few groups have demonstrated band edge photoluminescence ͑PL͒ in GaN films, grown by radio-frequency and direct-current ͑DC͒ magnetron sputter epitaxy ͑MSE͒.…”
mentioning
confidence: 99%